PENERAPAN FUNGSI MANAJEMEN DALAM KELOMPOK TANI CEMPAKA - Karamoy Reinal Ferdinan; Melsje Y. Memah; Grace A. J. Rumagit (Sam Ratulangi University, 2017)
The research aims to see how the implementation of management function in Cempaka farmer group in Meras Urban Village of Bunaken Sub-district of Manado City, by using Likert Scale concept to describe the implementation of management function which includes four functions (planning, organizing, implementation and evaluation). This research was conducted from February to June 2017. Data collection was primary data and secondary data. Primary data was obtained through direct interviews to 15 respondents using questionnaires and secondary data obtained from Meras Kelurahan Office. The sampling technique is Purposive Sampling that respondents are all members and managers of farmer group Cempaka. The resulting data is presented in tabular form and analyzed by Likert scale then described or describes the management function expectation in Cempaka farmer group. The results showed that the percentage of implementation of management function in Cempaka farmer group is 84,49% meaning the implementation of management functions that begin with planning work, finance or division of tasks in of each field to carry out what the work plan and evaluate the work of the group is in accordance with the function of management.*eprm*